Proceedings of v International Scientific Conference “Current State, Problems and Prospects of the Development of Agrarian Scie 2020
DOI: 10.33952/2542-0720-2020-5-9-10-86
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultivated strawberry micropropagation using а biogenic silica and green-tea-flavonoids-based mechanocomposite

Abstract: For the first time, organogenesis and physiological characteristics of Fragaria ananassa microclones (cvs. ‘Alpha’ and ‘Solnechnaya polyanka’) under the influence of mechanocomposite (MC) based on rice husks amorphous silica and flavonoids of green tea during the multiplication stage in in vitro conditions were studied. The addition of the MC (0.0, 2.5, 5.0 and 10.0 mg·L-1) to the Gamborg- Eveleg’s basal salt medium supplemented with 0.75 mg·L-1 6-benzylaminopurine has shown beneficial action on processes of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Green tea is rich in the flavanol group of polyphenols as catechins which may constitute up to 30% of the dry weight [6]. In previous studies, we have shown the growth-regulating and adaptogenic activities of the mechanocomposite based on biogenic silica and green tea flavonoids at the stages of in vitro rooting and ex vitro acclimatization of F. × ananassa plantlets [7][8]. Since mechanocomposite contains silicon compounds and catechins with antioxidant properties [9][10], in this work, for the first time, the potential antioxidant protective effect, including superoxide dismutase, catalase, and peroxidase enzymes, of this environmentally friendly preparation will be analyzed under micropropagation of strawberry.…”
Section: Introductionmentioning
confidence: 94%
“…Green tea is rich in the flavanol group of polyphenols as catechins which may constitute up to 30% of the dry weight [6]. In previous studies, we have shown the growth-regulating and adaptogenic activities of the mechanocomposite based on biogenic silica and green tea flavonoids at the stages of in vitro rooting and ex vitro acclimatization of F. × ananassa plantlets [7][8]. Since mechanocomposite contains silicon compounds and catechins with antioxidant properties [9][10], in this work, for the first time, the potential antioxidant protective effect, including superoxide dismutase, catalase, and peroxidase enzymes, of this environmentally friendly preparation will be analyzed under micropropagation of strawberry.…”
Section: Introductionmentioning
confidence: 94%